Membumikan Etika Sosial dan Pemahaman Multikultural Umat Beragama Melalui Pendidikan Tinggi - Andit Triono (LP2M IAIN Syekh Nurjati Cirebon, 2022)
ABSTRACTWhen looking at social interactions between communities, we cannot deny the presence of the influence of religious frames as the basis for people's thinking and acting. It is not uncommon for clashes between communities on the pretext of differences in religion and religious understanding that lead to multi-faceted conflicts as a result of globalization and